TENNIS ELBOW IN INDUSTRY. Issue 2 (April 1965) - Sinclair, A.
Abstract : This paper briefly reviews the present state of knowledge concerning the various factors involved in the aetiology of tennis elbow and the possible pathological lesions underlying the condition. Two series of cases are considered in greater detail. The first series, consisting of 37 cases, was treated by physical methods only, viz., manipulation, ultrasonic radiation, and short wave diathermy. The results were disappointing since little more than half the number were improved by sonation although subsequent diathermy did improve the majority of those who did not respond. But physical treatment is shown to be time consuming and variable in its results. The second series was treated by local infiltration of the painful area by hydrocortisone and, of the 38 cases, only one proved unsuccessful after one or two injections. The reduction in treatment-time and the fact that no special equipment is necessary are some of the obvious advantages in this form of treatment. The paper concludes with a discussion on the rationale of treatment and some additional aetiological factors which are in favour of an inflammatory, rather than a traumatic, basis for the condition.